Modifikasi Alat Pengering Biochar dengan Penambahan Tiga Buah Burner untuk Meningkatkan Efisiensi Pengeringan - Dika Zulfahmi (Fakultas Teknologi Pertanian, 2026)
Biochar drying is an important process in biochar production that affects drying efficiency and product quality. However, the existing biochar drying equipment experiences uneven heat distribution, resulting in less effective drying performance. This study aims to improve the performance of a biochar drying device by modifying it through the addition of three burners to enhance heat distribution and drying efficiency. The research was conducted using an experimental method by testing the modified dryer at different final operating temperatures. The observed parameters included drying efficiency, electrical energy consumption, and moisture content of biochar. The results showed that at final temperatures of 240 °C and 250 °C, the drying efficiency reached 68.16% and 75.38%, respectively, indicating effective utilization of input energy during the drying process. The addition of three burners successfully reduced heat distribution non-uniformity inside the drying chamber and improved the uniformity of biochar heating.
FINALISASI oleh Arif 2026 Juni 09
Keywords: biochar; biochar dryer; drying efficiency; burner modification